Maintaining Organizational Sustaincapability Towards Management Innovation Using Strategic Foresight - Wimber Jerry Panjaitan; Erlinda Sholihah; Iwan Koerniawan; Myra Andriana (Journal of Management and Informatics, 2022)
This study aims to examine the role of Strategic foresight and its capability to support the development of management innovation processes within organizations. This study uses a narrative literature review approach involving potential interactions of three main topics, namely: strategic foresight, management innovation, and management cognition. The research findings explain that every individual has a character from birth to being able to see the future. Then the capability for foresight in this organization must be developed and continuously maintained by both stakeholders in the organization's management and employees. Before implementing a foiresight strategy, it is necessary to understand in depth managerial cognition as the basis for its application. Furthermore, the development of a well-managed strategic foresight will become a management innovation so that it can maintain the sustaincapability of the organization. This conceptual paper lays a foundation that can be used as further research in determining strategic foresight abilities in relation to managerial dynamic abilities. The results of this paper can be used by organizations with a long history of facing challenges in capturing the challenges of changing business environment in the future.